2019
DOI: 10.1111/den.13381
|View full text |Cite
|
Sign up to set email alerts
|

Antireflux covered metal stent for nonresectable distal malignant biliary obstruction: Multicenter randomized controlled trial

Abstract: Background and Aim An antireflux metal stent (ARMS) for nonresectable distal malignant biliary obstruction (MBO) may prevent recurrent biliary obstruction (RBO) as a result of duodenobiliary reflux and prolong time to RBO (TRBO). Superiority of ARMS over conventional covered self‐expandable metal stents (SEMS) has not been fully examined. Methods We conducted a multicenter randomized controlled trial to examine whether TRBO of an ARMS with a funnel‐shaped valve was longer than that of a covered SEMS in SEMS‐na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
69
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(73 citation statements)
references
References 42 publications
1
69
2
1
Order By: Relevance
“…6A). Significant heterogeneity was noted (P=0.03, I 2 =72%) among the studies [7-9], best resolved when the study by Hamada et al [8] was excluded, while the new effect estimate showed a significant reduction in the overall incidence of stent dysfunction in favor of the AVRMS group. However, subgroup analysis by cause of dysfunction showed a greater frequency of stent migration (OR 2.76, 95%CI 1.24-6.17; P=0.01; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6A). Significant heterogeneity was noted (P=0.03, I 2 =72%) among the studies [7-9], best resolved when the study by Hamada et al [8] was excluded, while the new effect estimate showed a significant reduction in the overall incidence of stent dysfunction in favor of the AVRMS group. However, subgroup analysis by cause of dysfunction showed a greater frequency of stent migration (OR 2.76, 95%CI 1.24-6.17; P=0.01; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Hu et al concluded that ARVMS significantly reduced the risk of ascending cholangitis and had longer stent patency [7]. On the other hand, Hamada et al showed that ARVMS did not increase the time to recurrent biliary obstruction and was associated with a higher rate of stent migration [8].…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Conversely, another report did not find any advantage in terms of stent patency, when using anti-reflux valve metal stents. 20 The optimal anti-reflux valve design, including shape, material, and length, remains under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Misra et al reported that free reflux of barium occurred through the SEMSs in all patients in whom the SEMSs were placed across duodenal papilla. To prevent free reflux from the duodenum to the biliary system, several types of SEMSs with anti‐reflux system have been developed 5 . A recent multicenter randomized controlled trial by Hamada et al .…”
mentioning
confidence: 99%
“…A recent multicenter randomized controlled trial by Hamada et al . evaluated the superiority of the anti‐reflux metal stent (ARMS) (Niti‐S long‐covered ComVi stent; Taewoong Medical Inc., Seoul, Korea) over conventional CSEMS (Niti‐S ComVi stent; Taewoong Medical Inc.) for SEMS‐native patients with UMDBO 5 . This ARMS had a 7‐mm‐long funnel‐shaped valve made of expanded PTFE, including four 5‐mm‐long longitudinal nitinol wires to maintain its shape.…”
mentioning
confidence: 99%